Rancang Bangun Web Service API Aplikasi Jual Beli Barang Bekas Menggunakan Metode REST - Prakoso, Anang Bagus; Santiyasa, I Wayan (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
The development of Information Technology plays a very important role in human life and has made great progress in various aspects such as business. With the development of IT in the business aspect, various applications and services have emerged electronically, one of which is e-commerce. To support the process of data transactions in e-commerce, it is necessary to apply web service technology with safer data transactions, high interoperability, and users can access anytime and anywhere. The architecture used in the design of this research is REST. With the implementation of the REST architecture in the implementation of this research, the percentage of success is 100%. These results are obtained from the Blackbox test on conditions that are in accordance with the functional requirements of each function.